Dinamika pokazatelej mineral'noj plotnosti kostnoj tkani i gormonal'nogo profilja u sportsmenov velosporta na etapach godicnogo cikla podgotovki - Nikitina, K. I.; Abramova, T. F.; Nikitina, T. M.; Ovcharenko, L. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Changes in the secretion and metabolism of hormones that ensure the processes of adaptation to physical exertion can be a risk factor for impaired functioning of the bone tissue. The negative impact of intense muscle activity on bone mineral density (BMD) is reflected as an increase in injuries in athletes, one of the reasons for which are osteoporotic changes. The objective of this study is to study the relationship between the heel bone mineral density and hormonal parameters in highly skilled male representatives of the age in the age corresponding to the peak of bone mass at the stages of the annual training cycle. Measurements of BMD were carried out using quantitative ultrasound (QUS) of the heel by the Achilles Express device (Lunar, USA). The BMD level was estimated as a percentage of the peak norm for this skeleton site (T-score). It is shown that the dynamics of BMD at the stages of the annual training cycle is associated with changes in neurohumoral parameters. A decrease in BMD at the competitive period is associated with an increase in the secretion of catabolic hormones (cortisol, thyroxin) and a decrease in the level of anabolic hormones (testosterone, prolactin, GH, insulin).